Dodecyl α‐L‐Rhamnopyranosyl‐(1→2)‐β‐D‐fucopyranoside Derivatives from the Glandular Trichome Exudate of Erodium pelargoniflorum. Issue 6 (18th June 2013) - Sakai, Takaomi; Tanemura, Yuhei; Itoh, Satsuki; Fujimoto, Yoshinori
Abstract Chemical investigation of the glandular trichome exudate of Erodium pelargoniflorum (Geraniaceae) led to the isolation of two dodecyl disaccharide derivatives, named pelargoside A1 and pelargoside B1 (1 and 2, resp.). The structures of 1 and 2 were determined as dodecyl 4‐O‐acetyl‐α‐L‐rhamnopyranosyl‐(1→2)‐4‐O‐acetyl‐β‐D‐fucopyranoside and dodecyl 3, 4‐di‐O‐acetyl‐α‐L‐rhamnopyranosyl‐(1→2)‐4‐O‐acetyl‐β‐D‐fucopyranoside, respectively, by spectroscopic studies, including 2D‐NMR, and chemical transformations. In addition, undecyl, tridecyl, and tetradecyl homologs of 1 and 2, named pelargosides A2–A4 and pelargosides B2–B4, were also characterized as minor constituents of the exudate.